Membership Revocation for Members of the Egyptian People's Assembly According to the 1971 Constitution - Abbas, Amna khudair (Dirasat: Human and Social Sciences, 2025)
Objective: This paper attempts to shed light on the despoilment of membership of Egyptian Parliament members during 1976-1979 and be a run down to how does revocation against them had comprehended provisions of 1971 Egypt constitution. ‎ Method: This is a historical-analytical design to study reasons provided on the Membership Revocation for Members of the Egyptian People's Assembly, which comes because of the loss of credibility, and not performing the ‎obligations of the membership. Study data ‎were sourced from legislative documents and legal documents. This was followed by detailed case studies of Kamal ‎El-Din Hussein, Sheikh Ashour Mohamed Nasr, and Abdel Fattah Hassan. Results: There was a political motive behind these revocations. Kamal El-Din Hussein was thrown out for publicly denouncing the government ‎as it turned against Egypt's long-established Israeli peace treaty. Sheikh Ashour ‎Mohamed Nasr had been guilty of fomenting trouble in the Assembly, and Abdel ‎Fattah Hassan was banned — and never allowed to return — under a presidential ‎decree aimed at post-Revolution politicians. ‎‎ Conclusion: These results highlight the importance of constitutional and legal structures in controlling ‎political processes and ensuring the continued dominance of ruling factions. The research exposes the significance of electoral integrity and strategic use of legislative ‎mechanisms to the affordable to throttle the opposition. When a set of these results is combined with earlier research, it can help in understanding ‎the wider picture of the political and legal dynamics of the period.